Evaluation of age-related changes in human lens stiffness through a novel non-invasive method using Shear Wave Ultrasound Elastography (SWE) - Qader, Alaa Hussein; Bahari, Norafida; Abdul Rahim, Ezamin; Md Saleh, Rafidah; Mohamad Zain, Muhsonat; Kurdi, Amanj (Taylor and Francis, 2025)
Purpose: Presbyopia is an age-related condition characterized by diminished near-vision, primarily due to changes in the lens’ adaptive capacity. Shear Wave Ultrasound Elastography (SWE) offers a novel/noninvasive method to measure lens stiffness and could potentially enhance our understanding of presbyopia’s development. We aimed to use SWE to assess the elasticity of the human lens and explore the correlation between lens flexibility, age, presbyopia, and accommodation capacity. Methods: A cross-sectional analysis was conducted with 84 participants (mean age = 39.61 ± 9.60) from a government hospital in Serdang, Selangor, Malaysia. Eligibility was confirmed through refractive error and visual acuity tests. Selected participants underwent SWE scanning, and measurements of accommodation and presbyopia were taken. Statistical analysis included descriptive summaries and Pearson correlation coefficients to examine relationships between lens elasticity age, presbyopia, and amplitude of accommodation. Results: The analysis demonstrated a weak correlation between lens elasticity and age in nonpresbyopic group (r = 0.289) while positive strong correlation in presbyopic group (r = 0.674). A strong positive correlation was observed between lens elasticity and presbyopia in presbyopic group (r = 0.612). Moreover, there was a negative correlation with accommodation in both groups, (r = -0.358) for nonpresbyopic and (r = -0.493) presbyopic group. Conclusions: While lens elasticity diminishes with age, changes in ocular biomechanical properties impact lens function, particularly affecting near vision. Importantly, SWE is found to be an effective tool for assessing age-related changes in lens elasticity and presbyopia across various age groups, highlighting its potential for broader clinical application in diagnosing and understanding presbyopia.